Water quality index and sediment loading analysis in Pelus River, Perak, Malaysia - Hasan, Hasrul Hazman; Jamil, Nor Rohaizah; Norfadilah Aini, (Elsevier, 2015)
River can be considered as one of the main water, food source and habitat for all life forms. It is important to keep the health of river at an acceptable level for optimum function to support living being. The water quality index is used to assess the water quality condition in the river. Water quality index (WQI) and JPS River Index (JRI) can be used to monitor the health of the river. In this study, a total of eight stations along the main river were used for sampling. Six selected parameters (biological oxygen demand, chemical oxygen demand, dissolved oxygen, pH, suspended solid, and ammoniacal nitrogen) were used to calculate the water quality index. Parameters used to calculate JRI are specific flow, total suspended solid, total dissolved solid, and turbidity. Since sedimentation is a major threat in Pelus River, suspended solid concentration is used to find the sediment load in Pelus River. From the analysis, mean WQI in dry season (71.73) is higher compared to mean WQI in wet season (59.90). This indicates that the water quality during wet season (Class III-polluted) is a bit lower than the water quality during dry season (Class III-Slightly polluted). The sediment load in Pelus River per year is estimated to be 7.056 kg.ha/year during dry season and it is expected to be higher during wet season. The anthropogenic activities such as deforestation and agriculture were expected to influence the stability of the water quality in Pelus River